Large scale meta-analysis of urinary C-terminal telopeptide, serum cartilage oligomeric protein and matrix metalloprotease degraded type II collagen and their role in prevalence, incidence and progression of osteoarthritis. - Valdes, A; Meulenbelt, I; Chassaing, E; Arden, N; Bierma-Zeinstra, S; Hart, D; Hofman, A; Karsdal, M; Kloppenburg, M; Kroon, H; Slagboom, E; Spector, T; et al. (W.B. Saunders Ltd, 2014)
OBJECTIVE: To evaluate the role of three cartilage-derived biomarkers on osteoarthritis (OA): urinary C-terminal telopeptide (uCTX-II), serum cartilage oligomeric protein (sCOMP), and serum MMP degraded type II collagen (sC2M). SUBJECTS AND METHODS: Samples from 3582 individuals from the Rotterdam Study, the Genetics osteoArthritis and Progression (GARP), the Chingford Study and the TwinsUK cohort were assayed using enzyme-linked immune sorbent assays. Log10 of concentration levels were correlated with risk of hip, hand and knee OA, hip and knee OA severity and incidence, and progression of knee OA, adjusting for age, gender and body mass index (BMI). Results were meta-analysed to assess overall significance. RESULTS: After adjusting for covariates, sCOMP was associated with knee OA and hip and knee OA incidence. Furthermore, sC2M was associated with knee OA incidence and progression. After adjustment for multiple tests (Bonferroni P < 0.002) only the association between sCOMP and knee OA remained significant (odds ratio (OR) = 3.26 (95%CI 1.63-10.1) P = 0.0008 for each standard deviation (SD) increase in biomarker levels). Levels of uCTX-II were significantly associated with risk of hand, hip and knee OA, progression and incidence of knee OA. A receiver operating characteristics (ROC) analysis showed a consistent improvement in prediction of knee OA progression from an average area under the curve (AUC) is 0.646 for age, sex and BMI alone to an AUC = 0.668 including uCTX-II for prediction. CONCLUSIONS: uCTX-II is the most informative biochemical marker for prediction of OA. Both sCOMP and C2M showed some association with OA, thus indicating that they are descriptive of disease activity.